"We keep the nightmares in their cages": correctional culture, identity, and the warped badge of honor - Higgins, Ethan M. (Criminology, 2022)
Correctional scholarship has demonstrated concern over the dehumanizing implications of the carceral state for incarcerated people. This concern has been paralleled by an interest in understanding the work of prison staff and how correctional subculture may play an active role in prison dehumanization. By drawing from focus groups from all prisons in one state, we investigate how correctional staff construct and manage their identity through "us-them" ideologies. We find that staff leverage negative attitudes toward the incarcerated, and that these attitudes were underpinned by sensational cultural stories and epithets. Moreover, we find that staff use "othering" toward the incarcerated as a means to construct a warped badge of honor, which illustrates the burdens they bear from prison work and which frames themselves as heroes, guardians, and protectors. We conclude with a discussion of the implications of our findings, where we consider how dehumanization illustrates the mental coping work staff endure to carry out the symbolic violence and dehumanizing objectives of the carceral system.